Real-Time Scheduling Based on Nonblocking Supervisory Control of State-Tree Structures - Wang, Xi; Li, Zhiwu; Wonham, W. M. (IEEETransactions on Automatic Control, 2021)
This article presents a novel framework for the modeling and scheduling of real-time systems (RTS) processing both sporadic and (multiperiod) periodic tasks, based on nonblocking supervisory control of state-tree structures. Instead of assigning static priorities, a real-time scheduling mechanism, namely priority-free conditionally preemptive scheduling, is used to describe the preemption relation among the tasks processed in an RTS. As a dynamic priority scheduling mechanism, partially preemptive or nonpreemptive earliest-deadline first scheduling is also addressed in this article. Finally, the scheduling strategies are illustrated by real-world examples.
CRIS-Team WoS Importer:2021-09-10